Visions of the Earth: Colombian Indigenous Women Learning English from a Gender-Based and Multilingual Perspective - Velásquez-Hoyos, Angela Patricia; Giraldo-Martinez, Zoila Liliana (Íkala, Revista de Lenguaje y Cultura, 2024)
This case study is the result of a pedagogical intervention within the project Visions of the Earth in which 18 Colombian Indigenous women participated. Participants came from diverse Indigenous communities across different regions of Colombia. The project, Visions of the Earth, emerged as an initiative in collaboration with the Colombian Network of Indigenous Women in the Academia (RedColmia) and Universidad de Caldas. The project aimed to strengthen participants’ academic English through a year-long online program. Bi-monthly sessions were conducted by university professors and international guests, exploring visions of the Earth through texts by Indigenous writers who addressed historical exclusion and discrimination faced by Indigenous women in academia. Data were collected through two semi-structured surveys and participants’ artifacts. Despite debates on language erosion, participant perceptions underscore the importance of learning English as an empowering tool. Findings reveal that learning English under an Indigenous women gender-based perspective and multilingual approach is a medium for cultural appreciation, identity redefinition, and a means to share their unique perspectives on the Earth. This study provides insights into the intersection of language development, cultural identity, and academic empowerment for Indigenous communities.